PENGIKATAN JUAL BELI HAK ATAS TANAH YANG BERHUBUNGAN DENGAN PINJAM MEMINJAM YANG DI LAKUKAN DI HADAPAN NOTARIS (STUDI KASUS PUTUSAN NO 26/PDT 2016/PT-MDN) - RIADY RIADY (PREMISE LAW JURNAL, 2019)
Dosen pembimbing:1.  Prof. Dr. Muhd. Yamin, SH, MS, CN2.  Prof. Dr. Syafruddin Kalo, SH, MHum3.  Notaris Dr. Suprayitno, SH, MKn One of the problem in this case related to the land as the collateral given by the debitor to the creditor is not based on Law on Hypothecation but on the mutual agreement to make a sales contract before a Notary with additional agreement. The result shows that the legality of loan and credit is not correct if it is related to a plot of land as collateral by using Notarial Deed, because it has to refer to UUPA No. 4/1996 which has to be registered to the local Land Office. Meanwhile, legal protection for the parties involved in the agreement is that they can make a complaint against the Notary to the Supervisory Council as it is stipulated in Article 73 of UUJN. Those who are harmed can complaint against the Notary, personally, in criminal law, or in civil law. Legal protection for the Notary is in the form of repression as it is stipulated in the Decree of Menkumham No. 7/2016 on Notarial Honorary Council. There is no legal certainty on the position of loan and credit and right transfer because they are two different things and cannot be equalized, as it is stipulated in Article 1754 of the Civil Code.Keywords: Loan and Credit, Individual, Land Right Transfer